Now wait for last year - Dick, Philip K. (New York : Vintage Books, 1993)
Dr. Eric Sweetscent's life is spiraling out of control as his wife's addiction to a drug that sends her travelling through time takes control of her mind and pulls Eric into her madness while he struggles to care for the planet's most powerful man.
Adult.
Adult
Keywords: Drug addiction -- Fiction; Time travel -- Fiction; Drug abuse -- Fiction; Science fiction; Time travel -- Fiction; Science fiction